Fibronectin and Its Receptors in Hematopoiesis - Wirth, Franziska (Cells, 2020)
Fibronectin is a ubiquitous extracellular matrix protein that is produced by many cell types in the bone marrow and distributed throughout it. Cells of the stem cell niche produce the various isoforms of this protein. Fibronectin not only provides the cells a scaffold to bind to, but it also modulates their behavior by binding to receptors on the adjacent hematopoietic stem cells and stromal cells. These receptors, which include integrins such as α4β1, α9β1, α4β7, α5β1, αvβ3, Toll-like receptor-4 (TLR-4), and CD44, are found on the hematopoietic stem cell. Because the knockout of fibronectin is lethal during embryonal development and because fibronectin is produced by almost all cell types in mammals, the study of its role in hematopoiesis is difficult. Nevertheless, strong and direct evidence exists for its stimulation of myelopoiesis and thrombopoiesis using in vivo models. Other reviewed effects can be deduced from the study of fibronectin receptors, which showed their activation modifies the behavior of hematopoietic stem cells. Erythropoiesis was only stimulated under hemolytic stress, and mostly late stages of lymphocytic differentiation were modulated. Because fibronectin is ubiquitously expressed, these interactions in health and disease need to be taken into account whenever any molecule is evaluated in hematopoiesis.